ANALISIS FILOGENETIK FAMILI ZINGIBERACEAE & COSTACEAE BERDASARKAN PENANDA MATK DAN GEN PARSIAL - Topik Hidayat; Teressa Novita Evelyn; Nadya Rahma Widyanti; Nadia Nurul Fadhilah; Muhammad Zainal Arifin (Universitas Cokroaminoto Palopo, 2025)
This study analyzes the phylogenetic relationship between the Zingiberaceae and Costaceae families based on partial maturase K (matK) gene sequences and examines their common ancestry. A molecular systematic approach was applied, with DNA sequences aligned using ClustalX 2.1 and edited in BioEdit 7.0.5. Phylogenetic reconstruction was conducted using the maximum parsimony method in PAUP 4.0b10 with heuristic search and 1000 bootstrap replications. The results show a clear separation between Zingiberaceae and Costaceae, with Musa (Musaceae) as the outgroup. Costaceae is identified as the sister family of Zingiberaceae, indicating a shared ancestor. The paraphyletic nature of Costus and taxonomic anomalies likely reflect limited resolution of partial matK data.